Kajian Strategi Pemasaran Destinasi Wisata Warisan Budaya Dunia (WBD) Pura Tirta Empul Tampaksiring Gianyar - Nyoman Surya Wijaya; I Made Darsana; Ni Wayan Mega Sari Apri Yani (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The fluctuating number of tourist visits tends to decrease from 2020 to 2022. Studying the marketing strategy carried out by the world cultural heritage (WBD) manager of Tirta Empul Temple in Tampaksiring, Gianyar, is fascinating. This study aims to examine the marketing strategy model commonly used to determine the most significant factors influencing tourist visits to these tourist objects, which are leading tourist destinations. This study was designed with a descriptive and analytic approach, namely reviewing and analyzing the marketing strategy model used, then integrated with the results of the policy analysis of the Gianyar Regency Government in developing a marketing strategy for the WBD Pura Tirta Empul Tampaksiring tourist attraction to provide services to tourists. The study and research of the developed model for promotion found that e-commerce is the most potent factor, followed by word of mouth, publications, and advertising. For destination attributes, the most powerful factor influencing tourists to visit is the product of memories, location, available accommodation, ticket prices, and tourist attractions. At the same time, a fun, clean, safe, calm, new places, and a comfortable environment dominated by Place Branding. The most significant factor driving the decision to visit tourists is post-visit evaluation; this cannot be separated from the satisfaction felt after a previous visit. There are still differences in understanding in implementing the rules between the management, namely the Gianyar Regional Government as the first party and Pekraman Village as the second party, which can affect the quality of service and the level of tourist visits.